2019
DOI: 10.3390/metabo10010019
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mitochondrial Function in Idiopathic and Genetic Parkinson’s Disease

Abstract: Parkinson's disease (PD) is associated with brain mitochondrial dysfunction. High-energy phosphates (HEPs), which rely on mitochondrial functioning, may be considered potential biomarkers for PD. Phosphorus magnetic resonance spectroscopy ( 31 P-MRS) is a suitable tool to explore in vivo cerebral energetics. We considered 10 31 P-MRS studies in order to highlight the main findings about brain energetic compounds in patients affected by idiopathic PD and genetic PD. The studies investigated several brain areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In the current included studies, the abnormal expression of complex II, complex III, complex IV, and complex V in Parkinson's disease were varied [15,20,21,23,26]. Consistent with those data, previous studies showed that the alterations of complexes II-V in Parkinson's disease were diverse, which seemed to be remodeled in response to the complex I deficits [5,11,30]. The current included studies showed that treadmill training normalized the levels of neural mitochondrial complexes II-V, suggesting that treadmill training prevented the abnormal remodeling of complexes II-V in Parkinson's disease.…”
Section: Study Quality Evaluationsupporting
confidence: 83%
See 2 more Smart Citations
“…In the current included studies, the abnormal expression of complex II, complex III, complex IV, and complex V in Parkinson's disease were varied [15,20,21,23,26]. Consistent with those data, previous studies showed that the alterations of complexes II-V in Parkinson's disease were diverse, which seemed to be remodeled in response to the complex I deficits [5,11,30]. The current included studies showed that treadmill training normalized the levels of neural mitochondrial complexes II-V, suggesting that treadmill training prevented the abnormal remodeling of complexes II-V in Parkinson's disease.…”
Section: Study Quality Evaluationsupporting
confidence: 83%
“…To establish this issue, it is necessary to have an efficient method to measure the change of Parkinson's disease mechanisms during and after treadmill training. Recently, the evidence has suggested that 31 phosphorus-magnetic resonance spectroscopy ( 31 P-MRS) is a promised approach for the evaluation of mitochondrial function in Parkinson's disease patients in both the rest-stage and moving-stage [5]. Although the application of 31…”
Section: The Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies on mitochondrial impairment in PD are still scarce and lack intra-site reliability (e.g., by distinct hardware requirements), which is one major prerequisite for theranostic-accompanied drug trials (Dossi et al, 2019). The ongoing development of quantitative MRI/MRSI sequences and dual-calibrated fMRI (for MRI-based oximetry) will more than likely overcome the problem of inter-site reliability (Lara et al, 1993;Germuska et al, 2019).…”
Section: Recognising Prodromal Mitochondrial Dysfunction: Selection Omentioning
confidence: 99%
“…often show tissue-specific expression patterns and therefore lack biological interpretability in peripheral blood cells, e.g., peripheral monoclonal blood cells (PMBCs; Dossi et al, 2019;He et al, 2019). The determination of mtDNA mutation load is altered by the different proliferation rates of distinct cell types, which hinders the insights gathered from PMBCs to assess neuronal dysfunction (O'Callaghan et al, 2015).…”
Section: Blood Biomarkers Of Mitochondrial Dysfunctionmentioning
confidence: 99%